1998
DOI: 10.4037/ajcc1998.7.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Changing practice patterns for children with heart disease: a clinical pathway approach

Abstract: BACKGROUND: Pediatric cardiac care is costly and requires extensive resources. We studied the effect of clinical pathways on practice patterns and patient care outcomes in infants and children hospitalized for cardiac surgery. METHODS: In consecutive patients admitted for selected cardiac surgical procedures before (n = 69) and after (n = 173) implementation of clinical pathways, outcomes including hospital length of stay, days in the ICU, time to extubation, ordering of blood studies, costs, and readmissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
10

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
2
15
0
10
Order By: Relevance
“…The length of stay in the different hospital units was shorter in the fast-track protocol, in accordance with that reported in the literature 11 . However, the different authors who studied this issue focused more frequently on the length of hospital stay, the stay in the ICU, the length of postoperative hospitalization, and the duration of orotracheal intubation 11,13,16,23,27,28 . The other time intervals analyzed in this study, such as the length of preoperative hospitalization, which has psychological and clinical implications, even an effect on the skin bacterial flora, had not been previously assessed 29 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The length of stay in the different hospital units was shorter in the fast-track protocol, in accordance with that reported in the literature 11 . However, the different authors who studied this issue focused more frequently on the length of hospital stay, the stay in the ICU, the length of postoperative hospitalization, and the duration of orotracheal intubation 11,13,16,23,27,28 . The other time intervals analyzed in this study, such as the length of preoperative hospitalization, which has psychological and clinical implications, even an effect on the skin bacterial flora, had not been previously assessed 29 .…”
Section: Discussionsupporting
confidence: 90%
“…Although this study provided the opportunity to evaluate both protocols concomitantly, the allocation of patients into the protocols was not randomized, but this restriction has also been reported in other studies 5,11,13 . Other studies 11,13 reported in the literature changed the hospital routine, and comparisons were performed in regard to the experience prior to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, CPGs have been used with some success in the immediate postoperative management of selected congenital heart lesions reducing resource utilization, duration of hospitalization, and cost of postoperative care. [17][18][19] However, CPGs designed for longitudinal follow-up of children with congenital heart disease are sparse and do not include class indications or levels of evidence. 20 Not surprisingly in a field caring for rare and diverse lesions, pediatric cardiology is characterized by wide institutional and individual practice variation.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric cost-effectiveness literature describes research efforts that focus on prevention strategies such as prenatal care (2) and vaccination (3) and disease screening protocols. Pediatric cost analyses include critical pathways research to standardize care (4), study of direct and indirect costs to evaluate service utilization (5), and cost-effectiveness studies on alternative medication (6,7) or procedure (8 -11) regimens. There has, however, been little evaluation of the cost of pediatric rheumatic disease.…”
Section: Introductionmentioning
confidence: 99%